Faktor- Faktor yang Berhubungan dengan Penerimaan Makanan oleh Pasien di RSUD Dr. H. Ishak Umarella Provinsi Maluku - Zasendy Sendy Rehena (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2019)
Acceptance of food is less, can be caused by various factors both internal that the patient's health condition, or external that is the taste of food, food appearance and food service. The purpose of this research is to know factors - factors related to Acceptance of Food by Patients in RSUD dr .H. Isaac Umarella. The research method used is analytical method with Cross Sectional approach. Sampling using Total Sampling with sample size is 52 samples. Data collection using questionnaires and observation sheets. Data analysis included univariate and bivariate analyzes using computerized. The result of bivariate analysis showed that there was correlation between food taste and food acceptance by patient (P = 0,007), there was relationship between food appearance with food acceptance by patient (P = 0,004), there was no relation between food service and food acceptance by patient = 0.323). The conclusion in this research there is relationship between food taste and food appearance with food acceptance by patient and there is no relation of food service with acceptance of food by patient in RSUD dr. H. Ishak Umarella Year 2017. Patients are expected to consume food provided by the hospital until the nutritional value is fulfilled and accelerate healing.Â